Vascular Inward Rectifier K+ Channels as External K+ Sensors in the Control of Cerebral Blood Flow. (April 2015) - Longden, Thomas A.; Nelson, Mark T.
Abstract For decades it has been known that external K+ ions are rapid and potent vasodilators that increase CBF. Recent studies have implicated the local release of K+ from astrocytic endfeet—which encase the entirety of the parenchymal vasculature—in the dynamic regulation of local CBF during NVC. It has been proposed that the activation of KIR channels in the vascular wall by external K+ is a central component of these hyperemic responses; however, a number of significant gaps in our knowledge remain. Here, we explore the concept that vascular KIR channels are the major extracellular K+ sensors in the control of CBF. We propose that K+ is an ideal mediator of NVC, and discuss KIR channels as effectors that produce rapid hyperpolarization and robust vasodilation of cerebral arterioles. We provide evidence that KIR channels, of the KIR2 subtype in particular, are present in both the endothelial and SM cells of parenchymal arterioles and propose that this dual positioning of KIR2 channels increases the robustness of the vasodilation to external K+, enables the endothelium to be actively engaged in NVC, and permits electrical signaling through the endothelial syncytium to promote upstream vasodilation to modulate CBF.